2016
DOI: 10.1155/2016/3604842
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Circulating Cytokines Are Coelevated in Chronic Obstructive Pulmonary Disease

Abstract: Inflammatory biomarkers, including cytokines, are associated with COPD, but the association of particular circulating cytokines with systemic pathology remains equivocal. To investigate this, we developed a protein microarray system to detect multiple cytokines in small volumes of serum. Fourteen cytokines were measured in serum from never-smokers, ex-smokers, current smokers, and COPD patients (GOLD stages 1–3). Certain individual circulating cytokines (particularly TNFα and IL-1β) were significantly elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 33 publications
3
14
0
1
Order By: Relevance
“…Furthermore, it was revealed that in the COPD patients with various cardiovascular diseases, the number of non-emphysema patients was greater than the number of emphysema patients; however, there was no statistically significant difference among the different severities of emphysema. Previous studies on COPD patients with atrial fibrillation demonstrated that recurrent episodes of systemic and local chronic airway inflammation, as well as continuous increases of inflammatory mediators in the circulating blood, are important factors leading to arteriosclerosis and increased cardiovascular events caused by the dysfunction of vascular endothelium (26)(27)(28). In the present study, the levels of MMP-9 in COPD patients with cardiovascular disease were higher than those in patients without cardiovascular disease.…”
Section: Discussionsupporting
confidence: 41%
“…Furthermore, it was revealed that in the COPD patients with various cardiovascular diseases, the number of non-emphysema patients was greater than the number of emphysema patients; however, there was no statistically significant difference among the different severities of emphysema. Previous studies on COPD patients with atrial fibrillation demonstrated that recurrent episodes of systemic and local chronic airway inflammation, as well as continuous increases of inflammatory mediators in the circulating blood, are important factors leading to arteriosclerosis and increased cardiovascular events caused by the dysfunction of vascular endothelium (26)(27)(28). In the present study, the levels of MMP-9 in COPD patients with cardiovascular disease were higher than those in patients without cardiovascular disease.…”
Section: Discussionsupporting
confidence: 41%
“…Overall, cytokine concentration differences between groups were not statistically significant. However, the researchers uncovered that the total serum cytokine levels statistically correlated with GOLD-determined COPD severity [ 67 ]. Given the assay sensitivity and serum access, this may be a fruitful way to identify patient risks prior to phenotypic symptoms and exacerbations.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies (21)(22)(23)(24) reported that patients with cardiovascular disease, diabetes, depression, cancer, and other diseases can show accelerated progression of COPD, and that an increase of C-reactive protein, interleukin-6, interleukin-8, and other markers can also accelerate the process of COPD. The results of this study indicated that in COPD patients with more than three comorbidities, the status of the smoking group was not more severe than that of the nonsmoking group, and that according to CT types, the status of type M patients with more than three comorbidities was more severe than that of type A patients.…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences among the subgroups in the nonsmoking group, indicating that the inflammatory mediators produced by harmful substances in the smoke also aggravate the development of comorbidities in the circulation. Other studies (24,25) showed that in COPD patients with moderate and severe cardiovascular and metabolic diseases, a variety of inflammatory mediators exist in circulating blood. In the type M and type E smoking groups, the status of COPD patients with cardiovascular disease was more serious than that of type A patients; in the nonsmoking group, there were no differences among the three subtypes in COPD patients with cardiovascular disease, indicating that although patients had quit smoking, chronic inflammatory mediators persisted in the blood of those with COPD and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%